Pengaruh Locus Of Control Terhadap Kinerja Guru Melalui Kepuasan Kerja Guru SMA Negeri 11 Ambon Maluku - Rachma Atamimi; Pieter Rehata; Rafiah Amalia (Yayasan Jompa Research and Development, 2022)
The aim of the researcher was to determine the influence of locus of control on teachers through job satisfaction. This study uses a descriptive-analytic method whose aim is to obtain an overview of the locus of control on teacher performance through job satisfaction at SMA Negeri 11 Ambon teachers. The source used is primary data, namely data obtained directly from the object of research at SMA Negeri 11 Ambon. Based on the data obtained, conclusions can be drawn, namely, locus of control has an effect on teacher performance, there is a positive and significant influence on job satisfaction on teacher performance, and locus of control has a significant effect on teacher performance through job satisfaction